Analysis of Community Knowledge, Attitudes, and Experiences toward Preparedness for Initial Emergency Response in Karya Murni Village, Paguyaman District, Boalemo Regency - Ibrahim Suleman; Dewi Suryaningsi Hiola (PT Inovasi Pratama Internasional, 2026)
Emergency conditions can occur suddenly in the community and require prompt and appropriate initial management before victims receive assistance from health professionals. Community preparedness is influenced by knowledge, attitudes, and experience in dealing with emergency conditions. This study aimed to analyze the relationship between community knowledge, attitudes, and experience and preparedness for initial emergency response in Karya Murni Village, Paguyaman District, Boalemo Regency. This study used a quantitative method with a correlational analytic design and a cross-sectional approach. The sample consisted of 50 respondents selected using purposive sampling. Data were collected using a questionnaire and analyzed through univariate and bivariate analyses using the Chi-square test. The results showed that most respondents had moderate knowledge (40.0%), positive attitudes (62.0%), no experience in dealing with emergencies (56.0%), and were categorized as prepared (56.0%). The statistical test results showed that knowledge, attitudes, and experience were associated with community preparedness for initial emergency response. The most dominant factor associated with preparedness was attitude. This study concludes that community preparedness for initial emergency response is associated with knowledge, attitudes, and experience. Therefore, health education, first-aid training, Basic Life Support simulations, and community empowerment are needed to improve community readiness to provide an initial response in emergency conditions.